The morphological transformations of the rat tongue under the conditions of general dehydration. - L. N. Davydova; G. F. Tkach; V. Z. Sikora; O. S. Maksymova; D. V. Muravskyi (Морфологія, 2016)
Background. The pathology of water and electrolyte balance is quite often observed in clinical practice, while it may hinder or disrupt the structural and functional state of the human tongue. The objective is to identify the features of rat's tongue morphological changes under severe degree of general dehydration at the microscopic and ultrastructural levels. Methods. The experiment was performed on 20 white laboratory rats. The animals were divided into experimental and control group (10 rats respectively). A severe degree of general dehydration was modeled by A.D.Soboleva for rats from the experimental series. In the work investigation of the next morphometrical parameters was performed: papilla length, diameter of base and apex of papilla, diameter of taste bud, thickness of epithelium and the thickness of the keratinized layer, lamina propria thickness, keratinization index, mitotic index, the nuclear-cytoplasmic ratio of epithelial cells, diameter of arteriole, diameter of capillary, diameter of venule, arteriolar-venular coefficient, diameter of muscle fiber, width of endomysium, width of perimysium, the square surface of nucleus, the square surface of mitochondria, the volume of nucleus, the volume of mitochondria. Results. The impact of the severe degree of general dehydration has led to the reduction of epithelium thickness for 19,31 % (р = 0,0001), lamina propria thickness was reduced for 31,89 % (р = 0,0001), and also led to increase of the horny layer thickness of the epithelium for 11,75 % (р = 0,0007). The keratinization index increased regarding the benchmark for 38,34 % (р = 0,0001). The nuclear-cytoplasmic ratio of basal cells increased for 23,89 % (р = 0,0001), of spinous cells increased for 27,76 % (р = 0,0479) and of granulosa cells increased for 31,37 % (р = 0,027). The arteriolar-venular coefficient increased for 5,51 % (р = 0,1851). The diameter of muscle fiber reduced for 27,93 % (р = 0,0009), the width of endomysium reduced for 24,31 % (р = 0,048) and the width of perimysium – for 22,73 % (р = 0,0486). The diameter of myofibril and the volume of myosymplast nucleus reduced for 8,56 % (р = 0,0064) and 19,35 % (р = 0,028) respectively. The arteriole diameter, capillary diameter, venule diameter of tongue muscle reduced for 23,91 % (р = 0,0001), 41,26 % (р = 0,0003), 27,53 % (р = 0,0001) respectively. Conclusion. Severe degree of general dehydration leads to the atrophic changes in the epithelial cells of the tongue mucosa and disruption of keratinization process. Furthermore, it leads to the loss of regularity in cross-striation, excessive reduction of myofibrils, hypertrophic and destructive changes in the mitochondria of tongue muscle. These changes occur on the background of organ microcirculation disorders manifested by a significant narrowing of the vessel lumen, capillaries stasis and perivascular hemorrhages.